Short-time decay of the Loschmidt echo - Wisniacki, D.A. (2003)
Short-time decay of the Loschmidt echo was discussed. It is used to measure the sensitivity to perturbations of quantum evolutions. It was found that the characteristic time of the regime is well described by the inverse of the width of the local density of states.